THE STUDENTS’ PROFICIENCY ON ENGLISH PRONOUNCIATION - Mudrikatuz Zahro; Wulan Wangi; -, Tri Mulyati (LUNAR, 2025)
Having clear pronouciation is very important in order to build good communication. In English language teaching, the students frequently face some challanges and thus the teacher need to monitor the progress. This study aims to describe the pronunciation proficiency of the eleventh-grade students at MA Ibrahimy Kalipuro. Descriptive quantitative was used as the design and the respondents were taken through purposive sampling technique. The sample was 26 students. The data were collected through performance test. The students’ voices during performance test were recorded and then were scored. The data were presented in a percentage. The result of this study indicated that the avarage score of voiced consonants was 72 (fair)  while voiceless consonants was 69 (poor). Thus. It can be concluded that the teaching of pronounciation still need  further research in order to improve the students’ pronounciation proficiency. The teachers should be actively incorporate various startegies and media to assist the students practice English pronunciation regularly.